Cuidados enfermería en paciente con depresión post parto. - Mora Cadena, Ana Cristina (2024)
The development of this case study was based on the objective of applying the Nursing care process to a 24-year-old patient with postpartum depression. In which the analysis of the case is developed as a study methodology where the personal and family pathological history is determined, taking into consideration the reason for consultation and other relevant processes for the development of this case. Regarding the results obtained, the patient was monitored with control of adherence to the medication treatment prescribed by the doctor, evaluating mood changes, adverse effects, monitoring progress in behavior change and status. of the patient's mood which was proposed as a nursing intervention. In conclusion, the successful implementation of the nursing care process in a young 24-year-old mother who is experiencing depression after childbirth is essential to provide complete and personalized care, through a series of steps, such as evaluation, diagnosis, planning, intervention and evaluation.